Differences in beta-glucan levels in culture supernatants of a variety of fungi - ODABAŞI, ZEKAVER (OXFORD UNIV PRESS, 2006)
(1 -> 3)-beta-d-glucan is a well known cell wall constituent of fungal isolates that can be detected by assays in vivo and in vitro. Previous studies have shown that different fungal isolates may show different levels of reactivity with an assay for beta glucan. In this study we evaluated the in vitro reactivity of 127 clinical fungal isolates belonging to 40 different genera, with the Glucatell (TM) assay. The majority of the fungal isolates released high levels of beta glucan. Beta glucan test reactivity appears to be species-specific and this may reflect the beta glucan content of the organism.
Keywords: yeast; mould; beta glucan; diagnosis; supernatant; PLASMA; INFECTIONS; DIAGNOSIS; ASPERGILLOSIS; TRICHOSPORON; EPIDEMIOLOGY; LEUKEMIA